Analisis Semiotika pada Logo Hush Pupish dengan menggunakan Pendekatan Teori Robert Roland Barthes - Syakirina, Azza Akira; Yemima, Queen (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
Branding strategy plays an important role in building brand identity and attracting consumer attention. This research aims to analyze the visual elements in Hush Puppies branding with Roland Barthes' semiotic approach. The method used is qualitative-descriptive with analysis of visual signs, including logos, colors, and product designs, based on Barthes' three levels of meaning: denotation, connotation, and myth.  The results show that the Hush Puppies logo, which features a Basset Hound, denotatively depicts a dog with a calm expression. Connotatively, it symbolizes comfort, loyalty, and friendship, which is in line with the product's characteristics that are comfortable for everyday use. The use of neutral colors such as beige and brown creates a warm, simple and elegant impression. The casual and classic product design further strengthens the brand's identity as a symbol of a relaxed and practical lifestyle. At the mythical level, Hush Puppies is constructed as a brand that represents freedom, comfort and quality in everyday life.